Gestión administrativa – operativa y su incidencia en los productos y servicios que oferta la cooperativa de ahorro y crédito futuro lamanense año 2014, Propuesta de manual de funciones por competencias. - Cevallos Rosero, Williams Oswaldo (2016)
The present investigation was to evaluate the operational administration and its impact on the products and services offered by the credit union "Future Lamanense" Canton La Mana, during the period 2014 to present an alternative proposal for the process improvement and administrative activities. The methodology used was descriptive, analytical and documentary for which the application of research techniques was deemed necessary as the interview and survey. The results indicate that 46% of staff has no knowledge regarding the organizational structure and operating functions, sometimes the institution has designed processes and procedures aimed at achieving goals and objectives which have not been effectively disseminated to all staff, Cooperative marketing used to promote and disseminate the community financial products and services. During 2014 a total of 624 new partners grew, with the greatest demand microcredit, with a total of $ 2,784,110.00 in short term. In the application of indicators was determined that the quality of care is met by 83%, resolution of complaints with 76%, there is efficiency in transactions by staff of the pocket area, credit and collections has a compliance level of 88 % but recovery management portfolio it is quite poor. So by applying manual functions competency aspires to promote change in the Cooperative through effective dissemination of the roles and responsibilities of staff as well as the requirements for each job according to knowledge, experience and skill.